The oral vaccination with Paenibacillus larvae bacterin can decrease susceptibility to American Foulbrood infection in honey bees—A safety and efficacy study - Dickel, Franziska; Bos, Nick Maria Peter; Hughes, Huw; Martín-Hernández, Raquel; Higes, Mariano; Kleiser, Annette; Freitak, Dalial (Frontiers in Veterinary Science, 2022)
Pollination services to increase crop production are becoming more and more important, as we are facing both climate change and growing world population. High-density, commercial beekeeping has become a key link in the food supply chain and diseases have become a central issue in hive losses around the world. American Foulbrood (AFB) disease is a highly contagious bacterial brood disease in honey bees (Apis mellifera), leading to hive losses worldwide. The causative agent is the Gram+ bacterium Paenibacillus larvae, which affects honey bee larvae during first three days of their lives. It can be found in hives around the world with viable spores for decades. Once a hive shows clinical manifestation of the disease, the only effective way to eradicate it and contain the spread of the disease is by burning the hive, the equipment, and the colony. Because of its virulent nature and detrimental effects on honey bee colonies it is classified as a notifiable disease worldwide. Effective, safe, and sustainable methods are needed to help ensure the wellbeing of beehives. Even though insects lack antibodies, which are the main requisites for trans-generational immune priming (TGIP), they can prime their offspring against persisting pathogens. Here, we demonstrate an increased survival of infected honey bee larvae after their queen was vaccinated, compared to offspring of control queens (placebo vaccinated). These results indicate that TGIP in insects can be used to majorly enhance colony health, protecting commercial pollinators from deadly diseases and reduce high financial and material losses to beekeepers.